Reaction of soybean cultivars to Curtobacterium flaccumfaciens pv. flaccumfaciens, common bean strain - Maringoni, Antonio Carlos; Souza, Evandro Luiz Corrêa de (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the reaction of soybean cultivars EMBRAPA 46, EMBRAPA 47, EMBRAPA 48, EMBRAPA 58, EMBRAPA 59, EMBRAPA 60, EMBRAPA 61, EMBRAPA 62, BRS 66, BRS 132, BRS 133, BRS 134, BRS 135, BRS 136, BRS 155, BRS 156, BRS 157, IAC/BR-21, MG/BR-46 (Conquista), and MG/BR-48 (Garimpo RCH) to a strain of Curtobacterium flaccumfaciens pv. flaccumfaciens, isolated from common bean, using two inoculation methods, in greenhouse. All soybean cultivars showed low level of susceptibility to the bacterial strain, independently of the inoculation method used.